(untitled) (Journal of Informatics and Mathematical Sciences, 2020)
In this paper, we determine the ideal characteristics of highly connected firms in terms of the market structure and the network connectivity. The outcomes of the paper indicate that the performance of such firms is a function of each of the competition toughness and the network density. These findings emphasize the role of central firms in developing the R&D network structure in many empirical papers.